PHYTOCHEMICAL IDENTIFICATION AND ANTIOXIDANT ACTIVITY OF PASSIFLORA FOETIDA FRUITS AND LEAVES EXTRACTS: A COMPARATIVE STUDY - TANDORO, YOHANES; WIDYAWATI, PAINI SRI; BUDIANTA, TARSISIUS DWI WIBAWA; SUMARGO, GRACE (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The objective of this study was to compare the phytochemical composition and antioxidant activity of Passiflora foetida fruits and leaves extract. Methods: The parameters observed in this study were phytochemical compounds including alkaloid, flavonoid, phenolic, sterol, triterpenoid, saponin, tannin, and cardiac glycoside, total phenolic content Folin Ciocalteu method is based on reduction of Folin Ciocalteu reagent in alkaline medium; the metal complex produced measured at λmax: 760 nm; total flavonoids content with AlCl3 Colorimetric method based on complex formation of AlCl3 and flavonoid content in alkaline medium, the AlCl3-flavonoid complex produced measured at λmax: 510 nm; free radical DPPH scavenging activity; and ferric reducing power based on reduction of Fe3+ion into Fe2+ion that reacted with FeCl3 to form a ferric-ferrous complex that measured at λmax: 700 nm. Results: Passiflora leaves extract has phytochemical compound such as alkaloids, phenolics, flavonoids, saponins, and cardiac glycosides, total phenol was 22.92±0.18 mg GAE/g sample dry base, total flavonoid was 7.01±0.10 mg CE/g sample dry base, DPPH scavenging activity was 2.77±0.02 mg GAE/g sample dry base and ferric reducing power was 3.20±0.04 mg GAE/g sample dry base meanwhile Passiflora fruits extract had phytochemical compounds such as alkaloid, phenolic, flavonoids, cardiac glycosides, total phenol was 6.53±1.02 mg GAE/g sample dry base, total flavonoids were 1.56±0.27 mg CE/g sample dry base, DPPH free radical scavenging activity was 1.00±0.15 mg GAE/g sample dry base, and ferric reducing power was 1.12±0.17 mg GAE/g sample dry base. Conclusion: Passiflora leaves extract has higher total phenol, total flavonoid and antioxidant activity measured by DPPH scavenging activity and ferric reducing power value compared with Passiflora fruits extract.